Implementation of SQ3R in Teaching Reading at University - Anggraini, Dian (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2024)
Reading is the process of extracting and understanding the meaning contained in written materials, making it easier to comprehend, one of which is through SQ3R. SQ3R is a highly effective and productive learning strategy that includes five steps: survey, question, reading, recite, and review. The aim of this research is to describe the SQ3R method in reading instruction. This study employs a descriptive qualitative method. The result of this research is that SQ3R was an interesting method that can enhance students' motivation in Reading learning. The student survey stage involved providing reading material about reading, after which the students conduct a survey based on the text. The stage of questioning involves the lecturer guiding students to close the text that has been provided. Then, the students are instructed to create questions based on what they have obtained in the previous stage. In the Reading stage, the lecturer directs the students to read carefully and attentively while paying attention to the questions they have created. The Recite stage tests students' ability to recall answers by asking them to state the questions and answer them without looking at their notes. The review stage requires students to go over important notes and summarize the connections between the main points.